Joining empirical and modelling approaches to estimate dry deposition of nitrogen in Mediterranean forests. (December 2018) - García-Gómez, Héctor; Izquieta-Rojano, Sheila; Aguillaume, Laura; González-Fernández, Ignacio; Valiño, Fernando; Elustondo, David; Santamaría, Jesús M.; Àvila, Anna; Bytnerowicz, Andrzej; Bermejo, Victoria; Alonso, Rocío
Abstract: In Mediterranean areas, dry deposition is a major component of the total atmospheric N input to natural habitats, particularly to forest ecosystems. An innovative approach, combining the empirical inferential method (EIM) for surface deposition of NO3 − and NH4 + with stomatal uptake of NH3, HNO3 and NO2 derived from the DO3 SE (Deposition of Ozone and Stomatal Exchange) model, was used to estimate total dry deposition of inorganic N air pollutants in four holm oak forests under Mediterranean conditions in Spain. The estimated total deposition varied among the sites and matched the geographical patterns previously found in model estimates: higher deposition was determined at the northern site (28.9 kg N ha −1 year −1 ) and at the northeastern sites (17.8 and 12.5 kg N ha −1 year −1 ) than at the central-Spain site (9.4 kg N ha −1 year −1 ). On average, the estimated dry deposition of atmospheric N represented 77% ± 2% of the total deposition of N, of which surface deposition of gaseous and particulate atmospheric N averaged 10.0 ± 2.9 kg N ha −1 year −1 for the four sites (58% of the total deposition), and stomatal deposition of N gases averaged 3.3 ± 0.8 kg N ha −1 year −1 (19% of the total deposition). Deposition of atmospheric inorganic N was dominated by the surface deposition of oxidized N in all the forests (means of 54% and 42% of the dry and total deposition, respectively). The relative contribution of NO2 to dry deposition averaged from 19% in the peri-urban forests to 11% in the most natural site. During the monitoring period, the empirical critical loads provisionally proposed for ecosystem protection (10–20 kg N ha −1 year −1 ) was exceeded in three of the four studied forests. Graphical abstract: Image 1 Highlights: Dry deposition in Spanish Quercus ilex forests ranged 7.1–23.5 kg N ha −1 year - . Dry deposition represented 77% ± 2% of the total inorganic N input in these forests. Dry deposition occurred predominantly as surface deposition of oxidized forms. Reliable HNO3 measurements and LAI data are needed in forest monitoring networks. Abstract : Dry deposition of atmospheric N in four forests of Quercus ilex represented 77% of the total deposition of N and it was dominated by the surface deposition of oxidized N.